A contribution to the knowledge of Themus (Haplothemus) Wittmer from China (Coleoptera: Cantharidae) - Yang, Yuxia; Liu, Haoyu; Yang, Xingke (Zootaxa, 2018)
The Chinese fauna of Themus Motschulsky, 1858 is studied. Two new species are described: Themus (Haplothemus) quadratiformis sp. nov. (China: Shaanxi) and T. (H.) longideverticulum sp. nov. (China: Yunnan). Themus (Haplothemus) mishmiensis Wittmer, 1973 stat. nov. is elevated to the full-species rank from the subspecies of T. (H.) elongatior Pic, 1955, both species are redescribed. The male of T. (H.) quadratus Wittmer, 1983 and the female of T. (H.) weishanensis Kopetz, 2016 are described for the first time. The species are illustrated with aedeagus and habitus of male, abdominal sternite VIII and internal genitalia of female.